The Influence of Shadowing Technique to The Students Listening Ability - Dwi Andriani; Eka Agustina; Agung Setiadi; Muhammad Zainudin Afas (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
The objective to this research was to find out whether or not there was any significant difference between students who were taught listening by using Shadowing Technique and who were not taught by using Shadowing technique at the tenth grade students of SMK Muhammadiyah 3 Sukaraja. All of The tenth grade students of SMK Muhammadiyah 3 Sukaraja that consisted of 152 students was as population. By using purposive sampling, the sample was class X TKJ 1with total 34 as experimental class and X TKJ 2 with total 35 as control class. The data analysis was carried out by using Independent t-test for SPSS 25 version. The result shows that value of t-obt = 3.434 is higher than t-t = 2.000 and the P-out put of sign (2-tailed) is (0.001<0.05). Based on the result, it means that there is any significant difference between students who are taught listening by using Shadowing Technique and who are not taught by using Shadowing technique at the tenth grade students of SMK Muhammadiyah 3 Sukaraja.